RANCANG BANGUN MESIN PENCETAK PELET PAKAN TERNAK DENGAN PENGGERAK MOTOR LISTRIK - Andre Eka Rahayu (2023)
Feed supply is a major determinant of success in the livestock industry. Utilization of feed derived from agricultural, plantation and agro-industry residues is one way to meet the demand for ruminant animal feed. The purpose of this research is to develop a product for producing animal feed pellet machines from existing ones that can be used by corn farmers and breeders. Produce the manufacturing process applied (design, production stage, and component assembly) in making animal feed pellet molding machines. Knowing the material used, production costs, duration of time to manufacture, and quality of animal feed pellet production. The main drive of this animal feed pellet printing machine is an electric motor, using pulleys and belts to transmit motor power. The results of this study indicate that, when the engine was tested both with and without load, all of its components worked as they should. According to the trial results, this machine can make pellets with a diameter of 4 mm and a length of 3 mm. A manufacturing cost of IDR 5,002,000 is needed to design this animal feed pellet printing machine. The pellet molding machine produced has an output capacity of 10.23 kg per hour.